KEDISIPLIAN DAN KECERDASAN EMOSI PENGARUHNYA TERHADAP KINERJA PELAYANAN PEGAWAI INSTALASI REHAB MEDIK RSPAD GATOT SUBROTO - Triastuti, Yuli; Nurisnaini, Nurisnaini (JURNAL DARMA AGUNG, 2022)
The level of Discipline and Emotional Intelligence is one of the company's indicators in achieving the goal of improving performance. Therefore, the aim of the research is to know how the influence of discipline and emotional intelligence on performance at the Gatot Soebroto Army Hospital. The research was conducted through a quantitative approach to find out simultaneously and partial effect of discipline and emotional intelligence on employee performance at Gatot Soebroto Army Hospital. The population and samples taken are employees at the medical rehabilitation installation of Gatot Soebroto Hospital with a total of 59 respondents. Employees at the Gatot Soebroto Hospital's medical rehabilitation facility were given questionnaires as part of this study. The analysis of multiple linear regression is carried out through the F test and T test, two types of hypothesis testing. The study produced a multiple linear regression equation model, Y=1.479 + 0.187X1 + 0.463X2, that could be used to explain its impact of discipline and emotional intelligence on staff performance at Gatot Soebroto Hospital, with a R Square of 0.47. While the variables outside this study have an effect on the remaining 52.3%. When emotional intelligence and discipline have an impact on performance, the influence of both factors together is large, but only partially produces Discipline has a value of b1 = 0.187, implying that it has no significant impact on performance, whereas emotional intelligence has a value of b2 = 0.463, indicating that the more emotionally intelligent a person is, the better they perform at the Gatot Soebroto Army Hospital.